Cellular Heterogeneity and Cooperativity in Glioma Persister Cells Under Temozolomide Treatment - Rabé, Marion; Fonteneau, Lucie; Oliver, Lisa; Morales-Molina, Alvaro; Jubelin, Camille; Garcia-Castro, Javier; Heymann, Dominique; Gratas, Catherine; Vallette, François M. (Frontiers in Cell and Developmental Biology, 2022)
We have observed a drug-tolerant/persister state in a human glioblastoma (GBM) cell line after exposure to temozolomide, the standard-of-care chemotherapeutic agent for GBM. We used a multicolor lentiviral genetic barcode labeling to follow cell population evolution during temozolomide treatment. We observed no change in the distribution of the different colored populations of cells in persister or resistant cells suggesting that pre-existing minor subpopulations, which would be expected to be restricted to a single color, were not amplified/selected during the response to the drug. We have previously identified four genes (CHI3L1, FAT2, KLK5, and HB-EGF) that were over-expressed during the persister stage. Single-cell analysis of these four genes indicated that they were expressed in different individual cells ruling out the existence of a single persister-specific clone but suggesting rather a global answer. Even so, the transitory silencing of CHI3L1, FAT2, or KLK5 influenced the expression of the other three genes and the survival of U251 cells in absence of temozolomide. Since proteins encoded by the four genes are all localized in the extracellular matrix or interact within the extracellular compartment, we propose that cellular interactions and communications are important during the persister stage before the acquisition of chemo-resistance. Thus, persisters might be a new therapeutically relevant target in GBM.